1999
DOI: 10.1161/01.cir.100.10.1095
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Acutely Relaxes Rabbit Coronary Arteries In Vitro by an Estrogen Receptor–Dependent and Nitric Oxide–Dependent Mechanism

Abstract: These data demonstrate that raloxifene has vascular relaxing properties. The surprising finding is that the receptor-dependent effects via the endothelium are observed in coronary arteries from both male and female animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
4
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 51 publications
6
92
4
1
Order By: Relevance
“…In previous studies, either raloxifene or idoxifene was shown to cause vasorelaxation, mainly in a nitric oxide-dependent manner. 27,28 These differences between our data and other studies may be because of the differences of SERMs, target tissues, or animals.…”
Section: Discussioncontrasting
confidence: 88%
“…In previous studies, either raloxifene or idoxifene was shown to cause vasorelaxation, mainly in a nitric oxide-dependent manner. 27,28 These differences between our data and other studies may be because of the differences of SERMs, target tissues, or animals.…”
Section: Discussioncontrasting
confidence: 88%
“…30,31 Third, raloxifene acutely dilates rabbit coronary arteries via NO-and calcium influx-dependent pathways and increases uterine and coronary blood flow in ovariectomized ewes. 14,32 However, it has not yet been elucidated whether long-term treatment with raloxifene leads to reduced blood pressure and improved vascular function in hypertensive males. The presented data provide evidence that raloxifene treatment exerts vasoprotection in male SHR.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Raloxifene, a prominent member of the SERM family, has been shown to acutely improve endothelial function and to induce endothelium-dependent and -independent vasodilatation by NO release and calcium channel blockade in rabbit coronary arteries. 14 However, little is known about the long-term effects of raloxifene on vascular function.…”
mentioning
confidence: 99%
“…Cell shortening and the indo-1 ratio were measured in the continuing presence of 10 mM ICI 182,780 before and after the addition of 1 mM raloxifene. The concentration of ICI 182,780 chosen (10 mM) has previously been shown to be effective in inhibiting the acute relaxing effects of raloxifene on coronary arteries (Figtree et al, 1999).…”
Section: Effects Of Ici 182780mentioning
confidence: 99%
“…Animal studies investigating the effects of raloxifene on atherosclerosis have produced contradictory results (Bjarnason et al, 1997;Clarkson et al, 1998), while studies investigating the direct vascular actions of raloxifene have demonstrated beneficial effects. For example, raloxifene has been shown to exert acute, nongenomic, ER-mediated actions on rabbit coronary arteries and human umbilical vein endothelial cells through rapid activation of nitric oxide synthase (Figtree et al, 1999;Simoncini et al, 2002). In addition, raloxifene improves endothelial dysfunction and reduces blood pressure in spontaneously hypertensive male rats (Wassmann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%